STRATEGI KOMUNIKASI PEMASARAN PT GLOBAL DIGITAL NIAGA DALAM MENINGKATKAN BRAND AWARENESS MELALUI INSTAGRAM @BLIBLI.COM - Dinda Maharani Ika Yuliasari (Universitas Jayabaaya, 2022)
The use of Instagram as part of a marketing communication strategy has been done by many business people where marketing communication has an important role in increasing brand awareness among consumers through social media, especially Instagram. For this reason, the researcher wants to explain how promotional activities are carried out on Instagram social media and how the marketing communication strategy of PT. Global Digital Niaga to increase brand awareness through Instagram. The purpose of this study was to determine the form of marketing communication activities carried out through Instagram. The theory used in this research is New Media or New Media. The theory describes the development of media from the conventional to the digital era. The research method used is a descriptive method with a qualitative approach.